INHIBITY POWER OF HORN BANANA PEEL EXTRACT (Musa acuminata x Musa balbisiana) TOWARDS Candida albicans FUNGUS - Rizky efendi; Dina Trianggaluh; Aliyah Purwanti (Indonesian Pharmacopeia Journal, 2025)
Background: Candida albicans is the main cause of candidiasis, where treatment usually uses antibiotics and can cause side effects and resistance. Natural ingredients are chosen as an alternative treatment with low side effects, as for the phytochemical content therein such as, alkaloids, flavonoids, tannins, and saponins, capable of inhibiting Candida albicans fungi. Objective: This study aims to identify and analyze the inhibitory power of Horn banana peel extract extracted using maceration and sokhletasi methods against Candida albicans fungi. Method: This study included laboratory experimental research. Extraction of horn banana peel was carried out by maceration and soxhletation, both using ethyl acetate solvent. The extracts from maceration and soxhletation were each screened for phytochemicals.then tested its ability to inhibit Candida albicans by the well diffusion method. The concentration of extract used was 100% and 50%. As a comparison, a positive control in the form of nystatin suspension and a negative control in the form of 10% DMSO were used. Results: The average value of the extract yield from soxhletation, which is 5.5% is greater than the average value of the maceration yield, which is 2.72%. The average value of the inhibition zone diameter from the soxhletation extract of 100% and 50% and the maceration extract of 100% and 50% are 14.77 ± 0.08 mm; 10.28 ± 0.15 mm; 11.35 ± 0.18 mm and 7.06 ± 0.13 mm, respectively. The results of data analysis showed that there was a significant difference between the extraction method and extract concentration on the inhibition zone. Conclusion: The extracts from maceration and soxhletation were both able to inhibit the growth of Candida albicans fungus, where the soxhletation extraction method produced greater inhibitory power than the maceration extraction method.